2023
DOI: 10.4103/aian.aian_85_23
|View full text |Cite
|
Sign up to set email alerts
|

Association between Systemic Immune-Inflammation Index and Systemic Inflammation Response Index and Outcomes of Acute Ischemic Stroke: A Systematic Review and Meta-Analysis

Abstract: Systemic immune-inflammation index (SII) and systemic inflammation response index (SIRS) are being increasingly used to predict outcomes of various diseases. However, its utility for acute ischemic stroke (AIS) has not been established. Through this first systematic review and meta-analysis, we aimed to collate data on the prognostic ability of SII and SIRI for predicting functional outcomes and mortality after AIS. PubMed, CENTRAL, Scopus, Embase, and Web of Science were searched up to January 5, 2023, for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The association between SIRI, an inflammatory parameter, and some neurological disorders has been studied. Han et al 20 observed that SIRI predicted worse functional outcomes in ischemic stroke patients. Furthermore, a study showed that SIRI was linked to respiratory failure in GBS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The association between SIRI, an inflammatory parameter, and some neurological disorders has been studied. Han et al 20 observed that SIRI predicted worse functional outcomes in ischemic stroke patients. Furthermore, a study showed that SIRI was linked to respiratory failure in GBS patients.…”
Section: Discussionmentioning
confidence: 99%